Mentorship programmes in public primary schools: Beginner teachers’ perspectives. (International Journal of Scientific Research and Management (IJSRM), 2022)
Many beginner teachers experience the transition from student teacher to beginner teacher as challenging and a huge reality shock. These adapting demands are often daunting and they therefore need assistance to navigate the transition. The researchers argue that mentorship programmes can assist in addressing these transition challenges. The study makes the point that literature on teacher mentorship in South Africa has largely been from the perspective of administrators, designers and providers of mentorship programmes, rather than from the perspective of the beginner teachers themselves. The aim of the study was therefore to ascertain the perception of beginner teachers in public primary schools in the Ugu district of KwaZulu-Natal, South Africa, on mentorship programmes. The study was framed within the constructionist theoretical framework and made use of the qualitative approach, using structured interviews as a data collection instrument. The study revealed that beginner teachers experienced challenges with administration, classroom management and adjusting to the school environment. The findings further revealed that existing informal mentorship programmes failed to adequately address these challenges and meet beginner teachers’ professional needs. The researchers, however, argue that formal and well-designed mentorship programmes potentially have the ability to address the challenges beginner teachers encounter.